Trace element accumulation in the muscles of reef fish collected from southern new Caledonian lagoon: Risk assessment for consumers and grouper Plectropomus leopardus as a possible bioindicator of mining contamination. (December 2022) - Kumar-Roiné, Shilpa; Guillemot, Nicolas; Labrosse, Pierre; N'Guyen, Jean-Michel; Fernandez, Jean Michel
Abstract: Flesh of 141 fish specimens collected along the southern coast of New Caledonia, close to the mining industry Prony Resources New Caledonia, were analyzed for 10 elements (As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni and Zn). The leopard coral grouper Plectopomus leopardus revealed significant spatial variations for Cr, Fe, Mn and Zn and size-dependent accumulation of Hg. Sanitary risk assessment suggests that Hg and Me-Hg could potentially be a concern for heavy fish consumers. A previous study in New Caledonia had demonstrated the capacity of P. leopardus to differentially accumulate Ag, Cd, Cu, Hg and Zn and as such its potential as bioindicator specie to monitor contamination status in urban areas (Metian et al., 2013 ). Our results demonstrate that this specie can also to be used as a bioindicator to monitor the contamination status of Cr, Fe and Mn in New Caledonian lagoon in relation to mining activities. Highlights: Plectropomus leopardus reveals significant spatial variations for Cr, Fe, Mn and Zn and it size-dependence for Hg. A previous study in NC demonstrated the capacity of P. leopardus to accumulate Ag, Cd, Cu, Hg and Zn (Metian et al., 2013 ). Our results demonstrate that this species can also to be used as an indicator in relation to mining activities in N-Caledonia.